Effect of Different Previous Crops and Nitrogen Rate on Grain Sorghum (Sorghum bicolorL. Moench) - GUL, ISMAIL (Asian Journal of Chemistry, 2010)
The effect of previous crops (wheat, barley, lentil, Hungarian vetch and winter fallow) and different nitrogen rates (0, 120, 160, 200 and 240 kg N ha-1) on grain yield and yield components of grain sorghum (Sorghum bicolor L. Moench.) were examined under irrigated conditions in Diyarbakir, Turkey (subtropic) in 1999-2000, 2000-2001 growing seasons. Grain sorghum was grown in summers and wheat, barley, lentil and Hungarian vetch in winters. In the study, sorghum grain yield varied between 6833.8-9796.9 kg ha-1. It was determined that Hungarian vetch is suitable for previous crop and 160 kg N ha-1 N rate was the best nitrogen rate in grain sorghum production. According to interaction of previous crop-nitrogen rate, the highest yield was obtained from the subject grown after lentil with 160 kg N ha-1. Grain sorghum following legumes in rotation did not respond to applications more than 160 kg N ha-1, while barley-sorghum increased at all levels of N applied. Wheat-sorghum, fallow-sorghum did not respond to application more than 200 kg N ha-1.